A historiographical approach to Paul Perny's grammar of the Chinese language. (2nd January 2019) - Lee-Lee, Xavier; Trujillo-González, Verónica C.
ABSTRACT: This paper revisits, from a historiographical perspective, the Grammaire de la langue chinoise orale et écrite (1873–76) by French missionary Paul Perny, a fundamental and representative work of French missionary linguistics of the 19th century which, over the years, fell into oblivion. As a missionary grammar, we should also place it in a context of profound changes in which academic sinology strongly emerges under the auspices of French political interests in China. Moreover, through the study of several sources we will show how this work was received by the academic sinologists contemporary with Perny. This will allow us to address the relationship that this missionary linguist had with them. This research also focuses on another aspect, related to Perny's stance on the academic discussion dealing with the alleged inferiority of Chinese with respect to inflected languages, which was a widespread idea at that time.